Can quantity of technology use and Efl teachers’ teaching experience determine student engagement in language education? A quantitative replication and extension study - Betül Yoldaş (Journal of Language, Literature, Social and Cultural Studies, 2026)
The present quantitative research was intended to be written to replicate and extend a previous qualitative study by Yoldaş (2026) to make its results reliable and systematic through multiple linear regression analysis. Previous study focused on EFL teachers’ own technology use and its impact on their students’ engagement. Using JAMOVI software, previous results were transformed into numerical data with this study. A multiple linear regression analysis was administered to explore whether technology use frequency and teachers’ teaching experience had an effect on student engagement. Subsequent to data analysis, it was found that both variables had negative impact on student engagement in language education, proving that instead of focusing on teachers’ technology use frequency, quality of education should be taken into consideration to improve education. Even though pilot study limited the reliability and generalizability of the outcome due to its nature, the study gave insightful outcome for contemporary language teaching with statistical data.